2020
DOI: 10.1101/2020.12.11.420356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of established methods for DNA extraction and primer pairs targeting 16S rRNA gene for bacterial microbiome profiling of olive xylem sap

Abstract: Next Generation Sequencing has revolutionized our ability to investigate the microbiota composition of diverse and complex environments. However, a number of factors can affect the accuracy of microbial community assessment, such as the DNA extraction method, the hypervariable region of 16S rRNA gene targeted or the PCR primers used for amplification. The aim of this study was to assess the influence of commercially available DNA extraction kits and different primer pairs to provide a nonbiased vision of the c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Until now, comparative studies on the efficacy of DNA extraction kits for bacteria found on plants have been carried out mainly on terrestrial species, such as Arabidopsis thaliana (L.) Heynh., corn, soybean, or olives (Giangacomo et al, 2021; Haro et al, 2021). Bacterial community composition varies greatly among host species and is influenced by chemical and physical abiotic factors, such as the local environment, temperature, or water availability (Trevathan‐Tackett et al, 2020; Giangacomo et al, 2021; Sehnal et al, 2021), as well as by changes occurring during decomposition (Ma et al, 2020a).…”
mentioning
confidence: 99%
“…Until now, comparative studies on the efficacy of DNA extraction kits for bacteria found on plants have been carried out mainly on terrestrial species, such as Arabidopsis thaliana (L.) Heynh., corn, soybean, or olives (Giangacomo et al, 2021; Haro et al, 2021). Bacterial community composition varies greatly among host species and is influenced by chemical and physical abiotic factors, such as the local environment, temperature, or water availability (Trevathan‐Tackett et al, 2020; Giangacomo et al, 2021; Sehnal et al, 2021), as well as by changes occurring during decomposition (Ma et al, 2020a).…”
mentioning
confidence: 99%